Penerapan VCO (Virgin Coconout Oil) Terhadap Diaper Rash pada Bayi di Desa Gedangan Cepogo Boyolali - Wahyu Tri Lestari; Anjar Nurrohmah (Lembaga Pengembangan Kinerja Dosen, 2024)
Background : Diaper rash is considered a type of irritant contact dermatitis (Susanti, 2020). Based on data obtained from the Gedangan village Posyandu, there werw 6 cases of diaper rash in december 2023 in the Gedangan area. VCO is a non-pharmacological therapy to help prevent and treat diaper rash due to frequent use of diapers. Objective Describe the results of the implementation of VCO for diaper rash in babies in the village of Gedangan, Cepogo, Boyolali. Method: This research is a case study research using descriptive methods, namely by observing and interviewing two respondents suffering from diaper rash before and after the application of VCO. Results: There was a decrease in the characteristic value of diaper rash in An.S from a value of 4 to 0 while in An. D there was a decrease from a value of 2 to 0, which means there was no incidence of diaper rash. Conclusion : After implementing VCO on An.S and An. D there is a decrease in the characteristic values of diaper rash. This shows that VCO can prevent and treat diaper rash by reducing the characteristic value of diaper rash to no incidence of diaper rash.